The impact of hidden liquidity in limit order books - Stefan Frey; Patrik Sandås (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We report evidence that the presence of hidden liquidity is associated with greater liquidity in the order books, greater trading volume, and smaller price impact. Limit and market order submission behavior changes when hidden liquidity is present consistent with at least some traders being able to detect hidden liquidity. We estimate a model of liquidity provision that allows us to measure variations in the marginal and total payoffs from liquidity provision in states with and without hidden liquidity. Our estimates of the expected surplus to providers of visible and hidden liquidity are positive and typically of the order of one-half to one basis points per trade. The positive liquidity provider surpluses combined with the increased trading volume when hidden liquidity is present are both consistent with liquidity externalities.
urn:nbn:de:hebis:30-62275
Keywords: G10; G14; 330; Hidden Liquidity; Iceberg Orders; Hidden Orders; Reserve Orders; Limit Order Markets; Limit Order Books; Transparency; Wertpapierhandel; Marktliquidität; Börsenumsatz; Mikrostrukturanalyse; Theorie